The Legend of Laieikawai - Varez, Dietrich (University of Hawaii Press, 2004)
The twins Läieikawai and Läielohelohe are separated at birth but remain linked by their great beauty and a series of unscrupulous admirers and fickle husbands. Eventually the sisters are reunited with the help of a colorful cast of characters, including a man-eating lizard, a "cosmic" spider, and a giant bird, and find happiness at last in each other's company. This timeless kaao, or legend, of long ago is lovingly retold and illustrated here by renowned Island artist and storyteller Dietrich Varez